2020
DOI: 10.20944/preprints202009.0487.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Mortality Risk Assessment among Various Age Groups using Phylogenetic Analysis

Abstract: The age-related mortality and morbidity risk of COVID-19 has been considered speculative without enough scientific evidence. This study aimed to collect more evidence on the association between patient age and risk of severe disease state and/or mortality from SARS-CoV-2 infection. Genomic dataset along with metadata (3608 samples) retrieved from GISAID from different geographical regions were grouped into 10 age groups (0-10, 11-20, 21-30, 31-40, 41-50, 51-60, 61-70, 71-80, 81-90, 91-100 years) as well as hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73].…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73].…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
“…Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73]. The remaining 33 articles analyzed SARS-CoV-2 genomes downloaded from the GISAID or other available databases with patient status [8][9][10][11]20,21,[30][31][32][33][34][35][36]40,50,[52][53][54][55][56][57]…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations